Presence of mefA and mefE Genes in Streptococcus agalactiae - Arpin, C. (American Society for Microbiology, 1999)
Eighteen unrelated clinical isolates of Streptococcus agalactiae with the M phenotype harbored an mef gene. DNA sequencing showed that one of nine strains contained mefA (producing one amino acid substitution), whereas the remaining eight carried mefE (identity, 100%). Restriction analysis of PCR products indicated that the nine other strains also contained mefE.